2011
DOI: 10.1143/jjap.50.07hb07
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of LiNbO3 Single-Crystal Substrates Irradiated with Electrons

Abstract: Within the framework of second-order Rayleigh-Schrödinger perturbation theory, the effects of the interaction of the electrons and longitudinal optical phonons in low-dimensional semiconducting heterostructures can be investigated in a unified way. As a result, the ground-state energy for polarons confined in a general potential can be explicitly expressed as a one-dimensional integral. Moreover, some interesting problems, such as those of polarons in quantum wells, quantum wires, and quantum dots, can be read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Palatnikov et al observed the saturation of radiation-induced coloration during the defect annealing of doped and undoped LiNbO 3 materials [14]. Miyazaki et al analysed the influence of electron irradiation on the LiNbO 3 using photoacoustic spectroscopy (PAS), Fourier transform infrared (FTIR) spectroscopy, revealing that the composition of LiNbO 3 was a key factor to avoid the influence of the electron irradiation [15]. Tian et al investigated the influence of irradiation on the performance of LiNbO 3 with dosage of 6 MeV Xe 23+ , and found that the LN crystalline had an increased dielectric permittivity with high irradiation dose, but the effective piezoelectric coefficients of bulk LN crystalline nearly remained unchanged [16].…”
mentioning
confidence: 99%
“…Palatnikov et al observed the saturation of radiation-induced coloration during the defect annealing of doped and undoped LiNbO 3 materials [14]. Miyazaki et al analysed the influence of electron irradiation on the LiNbO 3 using photoacoustic spectroscopy (PAS), Fourier transform infrared (FTIR) spectroscopy, revealing that the composition of LiNbO 3 was a key factor to avoid the influence of the electron irradiation [15]. Tian et al investigated the influence of irradiation on the performance of LiNbO 3 with dosage of 6 MeV Xe 23+ , and found that the LN crystalline had an increased dielectric permittivity with high irradiation dose, but the effective piezoelectric coefficients of bulk LN crystalline nearly remained unchanged [16].…”
mentioning
confidence: 99%